Dilema Hukum: Mengurai Kompleksitas Wanprestasi dalam Perjanjian Pembiayaan Kendaraan Bermotor - Fatur Rahman; Aksah Kasim; Andi Heridah (Jurnal Litigasi Amsir, 2025)
This research aims to understand and analyze the legal aspects of breach of contract in motor vehicle financing agreements (A Case Study of Decision 6/Pdt.G.S/2022/PN Pre). This study employs a normative legal research method with a case study approach. The research findings indicate that as a legal consequence or sanction for a debtor who commits a breach of contract, they are liable to pay damages, have the agreement canceled, bear the risk transfer, and cover litigation costs. Based on the above description, it can be concluded that a breach of contract results in legal rights and obligations arising from a contractual relationship. In Indonesian law, there are two methods for resolving breach of contract disputes, namely through litigation and non-litigation pathways. Non-litigation dispute resolution involves methods like consultation, negotiation, mediation, or conciliation outside the court. In contrast, litigation is a dispute resolution process conducted in a court of law. As seen in the case of Decision 6/Pdt.G.S/2022/PN Pre, it was resolved through litigation, where the plaintiff, PT. BFI Finance Indonesia, Tbk Branch Parepare, sued Desy for alleged breach of the motor vehicle financing agreement